2012
DOI: 10.1177/0022002712445741
|View full text |Cite
|
Sign up to set email alerts
|

Rebel Interdependencies and Civil War Outcomes

Abstract: The article investigates how rebel interdependencies shape civil war outcomes. The author argues that alliances between rebel groups will have serious repercussions on the management of conflict. By examining civil war outcomes between 1946 and 2008, the author shows that the presence of multiple groups, alliances among rebels, the cumulative capabilities of one's allies as well as the credibility and the durability of alliances shape war outcomes. Rebels have the means to avoid government defeat and continue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 34 publications
0
66
0
Order By: Relevance
“…This is in spite of the fact that terrorist groups frequently interact, and the few studies to systematically examine these interactions have found important consequences (for example, Bloom ; Horowitz ). Civil war scholars are beginning to study relationships among subnational participants (for example, Bapat and Bond ; Pearlman and Cunningham ), and research suggests meaningful effects on war outcomes (Akcinaroglu ). It is unclear, however, whether terrorist groups are affected in the same ways as civil war participants.…”
mentioning
confidence: 99%
“…This is in spite of the fact that terrorist groups frequently interact, and the few studies to systematically examine these interactions have found important consequences (for example, Bloom ; Horowitz ). Civil war scholars are beginning to study relationships among subnational participants (for example, Bapat and Bond ; Pearlman and Cunningham ), and research suggests meaningful effects on war outcomes (Akcinaroglu ). It is unclear, however, whether terrorist groups are affected in the same ways as civil war participants.…”
mentioning
confidence: 99%
“…This suggests that multi-actor constellations matter because of strategic dynamics that arise between rebel organizations, not because such constellations are more difficult to resolve per se. In other words, our results bolster the strategic perspective through a more direct test of the full extent of strategic dynamics that is implied in, e.g., Cunningham (2006), Akcinaroglu (2012, but not adequately tested through measures of mere constellations.…”
Section: Results and Interpretationmentioning
confidence: 50%
“…We also include indicators of whether rebel organizations are splinter groups or are part of an over-arching alliance, accounting for particular dynamics that might be associated with fragmentation and coalition behavior Akcinaroglu, 2012;Christia, 2012). We code splinter and alliance characteristics based on the UCDP actor data (Petterson and Themnér, 2012) coding and using UCDP dyadic data to link this information (Harbom, Melander and Wallensteen, 2008).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, duration of civil conflict has been found positively associated with the number of violent groups. (see, among others, Cunningham, 2006;Cunningham, 2010;Akcinaroglu, 2012).…”
Section: On Multiparty Conflictsmentioning
confidence: 97%